Designing a Web Page to Improve Tutors’ Role in Nursing Students Formation - Juan Carlos Alvarado Peruyero; Zulema Bos Rodríguez; Nancy Ester Sosa Botana; Lourdes Montenegro Arias; Ariel Barceló Bos (Medisur)
Background: Higher Medical Education in Cuba is based on a work-related educational and pedagogical model. In this model, tutors play a key role, but their preparation to work with undergraduate nursing students is often insufficient. Objective: To design a web page containing the necessary information to improve tutors’ role in their work with undergraduate nursing students. Methods: descriptive research, conducted at the University of Medical Sciences of Cienfuegos from 2009 to February 2010. In order to identify tutors’ needs, a questionnaire and a diagnostic test were applied to 33,7 % of active-teaching tutors, randomly selected from a total of 169. During the second phase of this research contents for the web site were prepared and validated through expert criteria. Results: A website containing skills for each year and subject , curricula, skills control cards, existing resolutions and circulars, training strategies for work-related education, tutor’s functions, career curriculum, regulations for nursing practice, methodological instructions, organization of nursing curriculum and training to develop work-related education typologies was created. Conclusions: This website is a useful tool for monitoring nursing students during the work-related education process. It is available for tutors in their teaching settings and working places.